Experiments on grow out culture of groupers, Epinephelus malabaricus (Schneider) and Epinephelus tauvina (Forskal) - Nair, K V Somasekharan; Manojkumar, P P; Koya, K P Said; Suresh, V K (Indian Journal of Fisheries, 2011)
The results of the experiments conducted on the grow-out culture of the Malabar grouper Epinephelus malabaricus and Greasy grouper Epinephelus tauvina in three different culture systems such as brackish water earthern ponds, silpaulin lined ponds and FRP tanks during 1996-1998 are presented. In the earthern pond, from a mean size of 183 mm SE 21.67 and 137.9 g SE 4.78 in May 1997 E. tauvina attained 442 mm 4.25 and 1780 g SE 4.79 in March 1998 at the end of eleven months showing a daily growth increment of 0.78 mm and 4.97 g. In the silpaulin lined pond, E. malabaricus grew from an average size of 163.2 mm SE 2.96 (74.2 g SE 2.09 ) in April 1997 to 425.7 mm SE 3.65 (1170 g SE 4.67) in March 1998 registering a mean growth of 0.72 mm (3.04 g) per day. The average daily growth increment for E. tauvina in the FRP tank during the culture period was only 0.51 mm (1.53 g). The present investigations have shown the prospect of culturing groupers in the presently unutilised/underutilised estuarine and brackish water ponds.